Stepping In and Out of the International Market: Internationalisation of Technology-Oriented Firms in Germany and the UK - Helmut Fryges (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
For small high-tech firms international orientation is regarded as crucial for growth and long-term survival. Even newly founded technology based firms (NTBFs) are often internationally active shortly after their inception (?born globals?). However, in order to create jobs and have a sustainable influence on (macro)economic development, continuous growth of NTBFs is needed and research must focus on the continuous role of internationalisation. Based on longitudinal data, this paper examines empirically the long-term internationalisation behaviour of German and British technology-oriented firms founded between 1987 and 1996. Applying logit models, I am able to identify firm-specific success factors that influence the probability of entry into and exit from the international market. The results show, for instance, that firms can overcome high entry costs by acquiring firm-specific assets. Similarly, firm-specific resources prevent high-tech companies from exiting the international market. The strategic role of investment in R&D is stressed in particular by the data.
Keywords: L60; L80; L20; F23; 330; High technology industries; start-up; internationalisation; Klein- und Mittelunternehmen; Hochtechnologiesektor; Multinationales Unternehmen; Unternehmensgründung; Globalisierung; Erfolgsfaktor; Deutschland; Vereinigte Staaten